Advanced Vascular Access in Small Animal Emergency and Critical Care - Lee, Jack A.; Guieu, Liz-Valéry S.; Bussières, Geneviève; Smith, Christopher K. (Frontiers in Veterinary Science, 2021)
In canine and feline patients presenting in a state of hemodynamic collapse, obtaining vascular access can be challenging. Delays in achieving vascular access interfere with delivery of patient care. In human medicine, definitions of difficult vascular access are variable and include the need for multiple placement attempts or involvement of specialized teams and equipment. Incidence and risk factors for difficult vascular access have not been well studied in veterinary patients, which limits understanding of how best to address this issue. Alternatives to percutaneous peripheral or central intravenous catheterization in dogs and cats include venous cut-downs, umbilical access in newborns, corpus cavernosum access in males, ultrasound guided catheterization, and intraosseous catheterization. In recent years, advances in ultrasonography and intraosseous access techniques have made these more accessible to the veterinary practitioner. These vascular access techniques are reviewed here, along with advantages, limitations, and areas for future study of each technique.